Who owns Chinatown: Neighbourhood preservation and change in Boston and Philadelphia. (June 2018) - Acolin, Arthur; Vitiello, Domenic
The survival of Chinatowns and other ethnic enclaves in cities is largely determined by who owns property. Ethnic enclaves such as Chinatowns have traditionally played important economic, social and cultural functions as places for recent immigrants to live and work, though Chinatowns have long faced redevelopment pressures. In North America, as Chinese immigrants and their descendants settle in the suburbs, and as historic Chinatowns' locations close to revitalising downtowns attract increasing investment, the future of these historic enclaves is shaped by various, often intense and divergent, forces. This article describes changes in the patterns of property ownership in Boston and Philadelphia's downtown Chinatowns over the last decade (2003–2013) and relates them to changes and continuities in these neighbourhoods' population, commercial activities and building stock. The trends we observe simultaneously reinforce and complicate debates about gentrification and longstanding efforts to preserve these Chinatowns as ethnic Chinese residential, commercial, and cultural centres.